Characteristic and challenges of scandia stabilized zirconia as solid oxide fuel cell material In depth review - Arifin N.A.; Afifi A.A.; Samreen A.; Hafriz R.S.R.M.; Muchtar A. (Elsevier B.V., 2024)
Scandia-stabilized zirconia (ScSZ) has 1.53 times superior conductivity owing to its crystal structure as compared to yttria stabilized zirconia (YSZ). However, also due to this, ScSZ experienced phase structure transition which affects its stability when used as an SOFC electrolyte material and as anode. The typically ceria-doped 10 mol%ScSZ (10Sc1CeSZ) experienced Ce4+ ? Ce3+ transition in reduced environment led to lower fracture strength and instability. Alternative promising co-dopants to stabilized ScSZ phase, such as Nd, Sm and Gd are identified as a way forward in using ScSZ in reduced SOFC environment. The high affinity of the ScSZ oxide to Ni causes the dissolution of Ni in ScSZ grains and vice versa, thereby affecting the conductivity and material connectivity at the anode. The tolerance of Ni-ScSZ to hydrocarbon fuel and sulfur is significantly higher than that of Ni-YSZ and exhibited different behavior on carbon growth